Kiln-drying of Light Hardwoods for Packing Cases - Kapur, S. N. (Indian Forester, 1939)
Results of an investigation into the kiln-drying of light hardwoods for packing cases carried out at a seasoning installation recently built in Assam are briefly described. The drying time for Â½ inch thick tula (Tetrameles nudiflora) shooks was found to be as low as 30 to 36 hours. The cost of kiln-drying for an output of 120 tons of Â½ inch shocks per month comes to less than one anna per cubic foot. For heating and power purposes, the waste obtained in the factory is usually sufficient both for the mill and the kiln.